2019
DOI: 10.1177/0013161x19840398
|View full text |Cite
|
Sign up to set email alerts
|

How Principals Use a New Accountability System to Promote Change in Teacher Practices: Evidence From Italy

Abstract: Purpose: In Italy, only recently education policy makers have introduced a requirement for schools to implement the processes of self-evaluation, strategic planning and results’ reporting. In this article, we aim to explore how the new leadership approach of school principals in the context of the introduction of the new accountability system is affecting the practices of teachers. Research Method: Using quantitative data from an empirical study focused on the primary and secondary schools involved in a minist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 159 publications
0
24
1
Order By: Relevance
“…Instructional leadership can occur directly or indirectly. Leadership occurs directly when the principal works with teachers and other staff to develop the teaching learning process [13]. Meanwhile, instructional leadership indirectly occurs when the principal provides convenience and encourages teachers and staff to develop themselves, make decisions together, and change the school's values and vision leading to improved learning quality.…”
Section: Resultsmentioning
confidence: 99%
“…Instructional leadership can occur directly or indirectly. Leadership occurs directly when the principal works with teachers and other staff to develop the teaching learning process [13]. Meanwhile, instructional leadership indirectly occurs when the principal provides convenience and encourages teachers and staff to develop themselves, make decisions together, and change the school's values and vision leading to improved learning quality.…”
Section: Resultsmentioning
confidence: 99%
“…All the study variables were measured using a questionnaire previously validated by Paletta et al (2020) and reporting satisfactory psychometric properties. All items were rated on a four-point Likert scale ranging from 1 5 strongly disagree to 4 5 strongly agree.…”
Section: Methodsmentioning
confidence: 99%
“…Instructional leadership focuses on roles beyond the classroom, supporting the professional learning of peers, influencing policy/decision making, and ultimately targeting student learning (Wenner and Campbell, 2017). Empirical research has shown the linkage between instructional leadership, changes in teachers' practices and consequently, students' achievement (Hallinger et al, 2020;Paletta et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Principals such as school management, administrators, and leaders are central to school performance (Chua & Mosha, 2015; Kalkan et al, 2020). They allocate resources, build organizational capacity, and promote change (Paletta et al, 2020), influencing teachers’ perception, understanding, emotional commitment, and motivation (Lambersky, 2016; Spillane et al, 2002). Principals affect teaching indirectly through these influences on teachers, and they indirectly affect some of the types of washback, for example, teaching to the test.…”
Section: Theoretical Frameworkmentioning
confidence: 99%